Gentle Heart Program Reduces Temper Tantrums in Early Childhood Classrooms: Program Lembut Hati Menurunkan Temper Tantrum di Kelas Anak Usia Dini - Rusdiana, Yunita; Mahabbati, Aini (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Temper tantrums often occur in early childhood and can disrupt learning and social interaction in kindergarten settings. Specific background: At one kindergarten in Kaliorang District, repeated tantrums among students led teachers to develop structured strategies. Knowledge gap: Although tantrums are common, there is limited research exploring practical classroom-based programs designed by teachers themselves in Indonesian early childhood contexts. Aims: This study examines the structure, application, and challenges of the “Gentle Heart” program designed to manage temper tantrums in kindergarten. Results: Using a qualitative case study involving two experienced teachers over three months, findings show that the program reduces tantrum intensity and frequency through a calm–reflect–guide approach. Teachers allow emotional expression, wait for children to regain calm, and then engage them in reflective dialogue. Novelty: The study highlights a locally developed, teacher-led program that integrates emotional regulation strategies without external psychological intervention. Implications: The program offers a practical framework for early childhood teachers to manage tantrums in class, emphasizing the need for teacher assistants to sustain learning during tantrum episodes. Highlight Teachers apply structured emotional regulation steps to manage tantrums. The program shows reduced frequency and intensity of temper tantrums. Staffing support is essential for maintaining classroom learning flow. Keyword Temper Tantrum, Early Childhood Education, Emotional Regulation, Classroom Program, Teacher Strategies